On solitary wave solutions of a peptide group system with higher order saturable nonlinearity - İnç, Mustafa; Elhassanein, Ahmed; Abdou, Mohamed Aly Mohamed; Chu, Yu-Ming (De Gruyter Poland Sp Z O O, 2020)
In this article, a new continuous model of a peptide group system with higher order saturable nonlinearity is derived. The model is constructed up on discrete Schrodinger equation with higher order saturable nonlinearity. New exact solutions of the proposed model are investigated. Via the generalized Riccati equation mapping method travelling wave and soliton solutions are derived. For certain values of parameters kink, antikink, breathers, and dark and bright solitons are presented.
Keywords: Riccati equation mapping method; exact solutions; solitons; peptide system; saturable nonlinearity